(untitled) (Bangladesh Agronomy Journal, 2015)
An experiment was conducted at the Germplasm Centre, Department of Horticulture, Patuakhali Science and Technology University (PSTU) during the period from July 2011 to March 2013 to study the performance of selected mango rootstocks in the saline area in Bangladesh. The experiment consisted of four mango rootstock lines collected from Rangpur, Dumki, Khulna and Kuakata, and five salinity treatments namely control (0 dSm-1), low (4 dSm-1), medium (6 dSm-1), high (8 dSm-1) and very high (10 dSm-1). A two factor experiment was conducted in a Randomized Complete Block Design (factorial) with four replications. Results revealed that rootstock line and salinity levels had significant influences on various crop characters viz. length of rootstocks, diameter of rootstocks, number of leaves and percent rootstocks success and survivability. In case of rootstocks, the longest rootstock length (41.38 cm), highest number of leaves (37.58) and survivability (71.73%) were recorded in Rangpur line. In case of salinity treatments, rootstock diameter (16.09 mm), number of leaves/graft (36.47) and survivability (67.37%) were recorded in low salinity treatment. Interaction of rootstock lines and different salinity treatments showed significant variation on the length and diameter of rootstocks at 120 DAT. The maximum diameter of rootstock (17.63 mm) was recorded in high (8 dSm-1) salinity treatment in rootstock line of Kuakata, followed by the same stages of rootstock lines of Khulna (17.56 mm). The longest rootstock (46.75 cm) was recorded in control treatment (0 dSm-1) with rootstock line of Rangpur followed by the same stages of rootstock (41.75 cm) with medium salinity treatment (6 dSm-1). Rangpur rootstock line performed best from 0-8 dSm-1 salinity. The overall salinity tolerance was graded as follows: Rangpur rootstock line > Dumki rootstock line > Kuakata rootstock line > Khulna rootstock line. Bangladesh Agron. J. 2014, 17(1): 89-94